(untitled) (PerCursos, 2024)
The main goal of this work is to analyze Lenin and Gramsci’s formulations for education. The text is divided into four sections. Throughout the article, we present the links and affinities between Lenin and Gramsci, highlighting their continuities and differences. Furthermore, we address the theoretical-practical principle of hegemony from the perspective of Lenin and Gramsci regarding politics and knowledge production. Finally, we reflect on the current thinking of education in the context of the crisis of capitalism, considering the actions of reactionary and conservative forces that aim to sustain the imperialist system.